Utility of unmanned aerial systems for measuring plant height and plant vigor among several Georgia runner peanut cultivars. Issue 1 (11th October 2022) - Brown, Nino; Zhang, Jing; Maleski, Jerome; Schwartz, Brian; Branch, William D.
Abstract: Stand establishment, early‐season seedling vigor, and mid‐season canopy closure ensure peanut growers' timely achievement of a vigorous crop that can resist weeds, take advantage of available moisture and nutrients, and produce optimal yield. Direct measurement of these traits is prohibitively time consuming in large breeding trials and nurseries. Estimations based on visual ratings are rapid but require extensive training and experience for reliable data. Technological improvements in camera and unmanned aerial systems (UAS) has made them a practical and beneficial tool for plant breeders. This study evaluated the use of UAS for measuring plant growth‐related traits in a replicated yield trial of 16 Georgia runner‐type peanut cultivars. Flights were conducted at similar times with ground measurements and visual ratings of seedling and mid‐season plant vigor at the University of Georgia's Gibbs Research Farm in Tifton, GA, from 2019 to 2021. High correlations and similar ranks were seen between UAS‐derived and manual measurements for plant height among cultivars evaluated at mid‐season and late‐season ( r 2 = 0.95 and 0.75, respectively). For early‐season vigor evaluations, moderate correlations were achieved ( r 2 = 0.11–0.41), however, high correlations and similar results were evident comparing UAS‐derived mid‐season growth characteristics and visual vigor ratings ( r 2 = 0.75–0.86). Given the affordability and efficiency of data collection, UAS‐based phenotyping provides a promising and powerful tool for high throughput peanut breeding programs. Core Ideas: Aerial imagery was effective for evaluating lateral and vertical growth of Georgia runner‐type peanut cultivars. Measuring growth characteristics with unmanned aerial systems (UAS) is sufficiently accurate for high throughput phenotyping and selection of breeding lines. Runner peanut cultivars were reliably distinguished based on growth characteristics measured by UAS.